Application of the Mudhorobah Agreement in Sharia Farming Business Financing - Mutiara, Syadia; Abidin, Zaenal (Zabags Qu Publish, 2025)
Sharia financing, particularly through the mudharabah contract, offers a profit-sharing, interest-free capital alternative aligned with Islamic economic principles and is increasingly favored in the agricultural sector. This article aims to examine the effectiveness of mudharabah implementation in Islamic agricultural financing by employing a literature review method that incorporates scholarly sources and real-world practices. The findings indicate that mudharabah can serve as a fair and productive financing instrument when supported by transparency, accountability, and strong oversight systems. However, its implementation still faces challenges such as agricultural risks—like crop failure—and limited sharia financial literacy among farmers. The implications highlight the importance of enhancing education, fostering active involvement of Islamic financial institutions, and strengthening monitoring mechanisms to establish a sustainable Islamic agricultural financing ecosystem.